Effect of feeding rumen-protected lysine with different levels of soybean meal to growing steers - Wessels, R.H.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
To test the efficacy of rumen-protected lysine and methionine, six steers (486 lb) were used in a 6 4 incomplete Latin square design and fed corn-urea diets (85% concentrate) alone or supplemented with 2 or 4% soybean meal to give dietary crude protein levels of 12.5, 13.2, and 14.0% (as fed-basis). Each diet was fed with or without 5 g/day Smartamine-ML (rumen-protected lysine and methionine). Steers were fed to gain 2.6 lb/day. Nitrogen retention increased linearly, from 30.7 g/day (0% soy) to 35.5 g/day (4% soy) as the level of soybean meal and, thus, crude protein, increased in the diet. Supplementing steers with lysine had no effect on nitrogen retention. Total tract organic matter digestibility was similar for all treatments. No protein level lysine interaction occurred. We conclude that lysine was not the first limiting amino acid in the corn-urea soybean meal diets used in this study.
Keywords: Beef; Rumen-protected lysine; Soybean meal; Steers